2018
DOI: 10.26717/bjstr.2018.04.0001032
|View full text |Cite
|
Sign up to set email alerts
|

Seizures Related to Antibiotic Use: Update

Abstract: We did a non-systematic review of articles on the Google Scholar platform from January 1992 until February 2018.Preference was given to articles in Portuguese or English whose title presented the descriptors "seizures" or "epilepsy" associated with the most commonly used classes of antibiotics: penicillins, cephalosporins, quinolones, carbapenems, metronidazole and isoniazid. From this Abstract Objective: make a review about the risk of seizures related to the use of antibiotics. Method: We perform a non-syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…GABA receptors are categorized into GABA A (GABA A R) and GABA B receptors (GABA B R). Studies have found that GABA A R is the main type of receptor responsible for the pro-convulsive effects of βlactams, featuring both non-competitive inhibition and voltage-dependent changes [12]. The β-lactam ring structure is an important determinant of the epileptogenic properties.…”
Section: β-Lactamsmentioning
confidence: 99%
See 3 more Smart Citations
“…GABA receptors are categorized into GABA A (GABA A R) and GABA B receptors (GABA B R). Studies have found that GABA A R is the main type of receptor responsible for the pro-convulsive effects of βlactams, featuring both non-competitive inhibition and voltage-dependent changes [12]. The β-lactam ring structure is an important determinant of the epileptogenic properties.…”
Section: β-Lactamsmentioning
confidence: 99%
“…Cephalosporins are competitive antagonists of the GABA A receptor. Besides GABA inhibition, another mechanism involves glutamatergic Nmethyl-D-Aspartate (NMDA) receptor agonism [12]. Among the cephalosporins, cefazolin and cefepime are most strongly associated with seizure-triggering properties.…”
Section: Cephalosporinsmentioning
confidence: 99%
See 2 more Smart Citations